Method for preparing polydextrose from glucose liquid - LIU ZONGLI; LI KEWEN; XIAO YUJING; LUAN QINGMIN; XIAO ZHAOLING (2017)
The invention discloses a method for preparing polydextrose from glucose liquid. The method comprises the following steps: (1) cleaning starch with liquefied and saccharified glucose liquid through a granular carbon column; (2) performing nanofiltration of the glucose liquid, and removing disaccharide and polysaccharide substances therein; (3) performing vacuum concentration of the glucose liquid, adding sorbitol and citric acid, and performing high-temperature condensation polymerization to obtain a crude product of polydextrose; and (4) performing decoloration, ion exchange, concentration and drying of the crude product of polydextrose to obtain a finished product of glucose. In the invention, the glucose liquid prepared by saccharifying common starch serves as a raw material and is cleaned by granular carbon and through nanofiltration to obtain high-purity glucose liquid which is subjected to condensation polymerization, and the prepared finished product of polydextrose has good quality; and compared with